Workload Analysis and Determination of Financial Service Employee Requirements using the Full-Time Equivalent Method - Rivelia Maryani; Rani Aulia Imran; Katon Muhammad; Tri Wisudawati (Performa: Media Ilmiah Teknik Industri, 2025)
Company performance is supported by employee productivity, so an ideal workload is one way to maintain good company performance. PT. XYZ is a company engaged in financial services. Interviews with several employees revealed overlapping work, despite each having their job description. This imbalance in employee workload potentially leads to excessive workloads. This study aims to determine the workload received by PT employees. XYZ and choose the required number of employees based on workload calculations. This study uses the full-time equivalent (FTE) method, which analyzes workload based on employee working time converted into an FTE index value. The results show that 17% of employees have an inload workload, 33% are overloaded, and 50% are underloaded. When evaluated based on the field of work, workload equalization needs to be carried out. The separation of work involves adding two employees in the General and Participant Service division and one employee in the Administration and Membership division and reducing two employees in the Finance and Accounting division. Equalizing the workload needs to be done to help employees be more effective and productive in their work.